High-stability ZrxWyV1-x-yO2 / TiO2 double-layer film for intelligent window coating and preparation method

By adopting the ZrxWyV1-x-yO2/TiO2 double-layer film structure in the smart window material, the problem of insufficient thermal discoloration performance of VO2 film at room temperature is solved, and a smart window material with high stability and excellent optical performance is achieved.

CN119753574APending Publication Date: 2025-04-04HUBEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411871755.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing VO2 films have insufficient thermal discoloration performance at room temperature, low visible light transmittance, high phase transition temperature, poor durability and poor appearance aesthetics, making it difficult to widely use in smart window materials.

Method used

The ZrxWyV1-x-yO2/TiO2 bilayer thin film structure is adopted, and the optical band gap is increased by replacing V4+ ions by Zr4+ ions, the W6+ doping increases electron concentration and reduces the phase transition temperature, and a TiO2 anti-reverse layer is introduced on the ZrxWyV1-x-yO2 layer to adjust optical performance and stability.

Benefits of technology

The high-stability ZrxWyV1-x-yO2/TiO2 double-layer film is achieved with excellent optical performance, the metal-insulator transition temperature is close to room temperature, which improves the visible light transmittance and infrared light modulation ability, and enhances the stability and aesthetics of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753574A_ABST
    Figure CN119753574A_ABST
Patent Text Reader

Abstract

The invention discloses a high-stability Zr < x > W < y > V < 1-x-y > O < 2 > / TiO2 double-layer film for an intelligent window coating and a preparation method thereof. The bottom layer of the ZrxWyV1-x-yO2 / TiO2 double-layer thin film is a ZrxWyV1-x-yO2 functional thin film layer, x is greater than 0 and less than 1, y is greater than 0 and less than 1, and the top layer of the ZrxWyV1-x-yO2 / TiO2 double-layer thin film is an anatase-phase TiO2 anti-reflection layer. According to the ZrxWyV1-x-yO2 / TiO2 double-layer film provided by the invention, the optical band gap of VO2 is widened through Zr < 4 + >, so that the visible light transmittance of the film is effectively improved; on the other hand, by doping W < 6 + > ions in VO2 to introduce redundant carriers, VO2 IMT phase change is easy to occur, so that the phase change temperature is reduced, and by optimizing and regulating the doping content of Zr < 4 + > and W < 6 + >, the ZrxWyV1-x-yO2 functional film has low phase change temperature and high visible light transmittance; in addition, by introducing the TiO2 anti-reflection layer, the optical modulation performance of the ZrxWyV1-x-yO2 functional film can be further improved, meanwhile, the ZrxWyV1-x-yO2 functional film is protected from being oxidized, and the stability of the ZrxWyV1-x-yO2 functional film is improved
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of semiconductor optoelectronic materials, and in particular to a high-stability ZrO2 for smart window coatings. x W y V 1-x-y O2 / TiO2 double-layer film and preparation method thereof. Background Art

[0002] With the rapid development of society and economy, energy consumption in modern society has increased dramatically. Among all energy consumption, building energy consumption accounts for 30-40%. Glass units are an important part of building structures, providing landscape, natural light and solar energy for the interior space of buildings. Compared with other building components, glass units have poor thermal performance, and about 50% of the total energy consumption in buildings is generated by heat dissipation through glass windows. Therefore, reducing the energy consumption of glass windows is the key to achieving efficient energy saving in buildings. If thin film materials with thermochromic properties are widely used in building glass to achieve dynamic regulation of sunlight and intelligent temperature control, this will significantly optimize indoor temperature management, thereby reducing the use of air conditioners and achieving the goal of energy saving and emission reduction.

[0003] VO2 has a low insulator-metal transition (IMT) temperature, i.e., critical temperature T, close to room temperature (RT). c , and has become one of the most promising candidates for thermochromic materials. As a thermochromic material, VO2 has a phase transition temperature below (T <T c , T c ≈68℃) is a monoclinic structure (M, P21 / c), showing the characteristics of high resistivity, high visible light transmittance and low infrared light reflectivity; above the phase transition temperature (T>T c ), VO2 transforms into a tetragonal rutile structure (R, P42 / mnm), at which point its infrared light reflectivity increases significantly, while its transmittance and absorptivity decrease. Using this phase change property of VO2, sunlight, especially infrared light, can be effectively modulated. However, there are still many challenges in achieving large-scale commercial production of VO2 as a smart window material, such as the T c Above room temperature, visible light transmittance (T lum ) is low, solar modulation capability (ΔT sol ) insufficient, poor durability, and lack of aesthetic appearance (brown-yellow in color).

[0004] Based on the above-mentioned defects of VO2 thin film, it is necessary to regulate and improve its performance. Summary of the invention

[0005] In view of this, the present invention provides a high stability Zr for smart window coating x W y V1-x-y O2 / TiO2 double-layer film and its preparation method are used to improve the visible light transmittance of the existing VO2 film, reduce its phase transition temperature to near room temperature, and improve the stability of the film and the color of the film.

[0006] In the first aspect, the present invention provides a high stability Zr for smart window coatings. x W y V 1-x-y O2 / TiO2 double-layer film, the chemical formula of the double-layer film is Zr x W y V 1-x-y O2 / TiO2, wherein 0<x<1, 0<y<1.

[0007] In a second aspect, the present invention also provides a high stability Zr coating for smart window x W y V 1-x-y The preparation method of O2 / TiO2 double-layer film is as follows:

[0008] providing a substrate;

[0009] The Zr is prepared on the substrate surface by pulse laser deposition, magnetron sputtering or electron beam evaporation. x W y V 1-x-y O2 functional film.

[0010] Optionally, the thin film is prepared by pulsed laser deposition, and the specific steps are as follows:

[0011] Zr and W co-doped V2O5 ceramics were used as targets. The targets and substrates were placed in a vacuum chamber and evacuated to 10 -3 ~10 -4 The temperature of the substrate is controlled to be 300-800°C, the pulse laser energy is 200-600 mJ / Pulse, and the oxygen pressure is 0-10 Pa, and the Zr is deposited on the surface of the substrate. x W y V 1-x-y O2 functional film.

[0012] Optionally, the preparation method of the Zr and W co-doped V2O5 ceramic is as follows:

[0013] Weigh ZrO2, WO3, and V2O5 powders according to molar ratio and place them in a ball milling jar, mix them evenly, and then place them in a planetary ball mill and mill them for 4 to 6 hours to obtain a mixed powder;

[0014] The mixed powder is placed in a vacuum drying oven at 80-120° C., dried for 8-10 hours, then crushed and pressed into a round embryonic piece with a diameter of 27.5 mm and a thickness of 2 mm; the round piece is then placed in a vacuum tube furnace and fired at 600-700° C. for 6-8 hours to obtain Zr and W co-doped V2O5 ceramics.

[0015] Optionally, the substrate is a c-plane sapphire substrate or a glass substrate.

[0016] Optionally, the Zr x W y V 1-x-y Before the O2 film is formed, the substrate is ultrasonically cleaned with acetone, ethanol and deionized water respectively for 15 minutes. After cleaning, the substrate is blown dry with nitrogen.

[0017] Optionally, Zr is deposited on the surface of the substrate. x W y V 1-x-y The O2 film time is 10 to 60 minutes.

[0018] Further in the Zr x W y V 1-x-y The TiO2 anti-reflection layer film is prepared on the surface of the O2 layer by adopting a pulse laser deposition method, a magnetron sputtering method or an electron beam evaporation method.

[0019] Preferably, the specific steps of preparing the TiO2 anti-reflection layer film by pulsed laser deposition are as follows:

[0020] TiO2 ceramics are used as target materials. The substrate temperature is controlled to be 25-200°C, the pulse laser energy is controlled to be 200-600mJ / Pulse, the oxygen pressure is controlled to be 0-10Pa, and the Zr x W y V 1-x-y The TiO2 anti-reflection layer film is deposited on the surface of the O2 layer.

[0021] Optionally, in the Zr x W y V 1-x-y The time for depositing the TiO2 anti-reflection layer on the surface of the O2 layer is 30 to 60 minutes.

[0022] Furthermore, in the above technical solution, the Zr x W y V 1-x-y The thickness of the O2 layer is 70-110 nm, and the thickness of the TiO2 anti-reflection layer is 0-200 nm.

[0023] The present invention provides the above-mentioned high stability Zr for smart window coating x W y V 1-x-y The principle of O2 / TiO2 double-layer film with excellent optical properties, phase change temperature regulation function and high stability is as follows:

[0024] The Zr prepared by the present invention x W y V 1-x-y The O2 / TiO2 double-layer film uses the characteristic that the band gap of ZrO2 (5eV) is larger than the band gap of VO2 (2.5eV). 4+ Ion partially replaces V 4+ ions to increase the optical band gap of VO2, thereby effectively improving the visible light transmittance of the film. 6+ Doping increases Zr x W y V 1-x-y The electron concentration of the O2 film makes it easier for the film to transition from the insulating phase to the metallic phase, thereby achieving the purpose of lowering the phase transition temperature of the film. x W y V 1-x-y O2 thin film optical modulation performance, the present invention is in Zr x W y V 1-x-y Based on the O2 functional film, a TiO2 anti-reflection layer is introduced to construct a Zr x W y V 1-x-y O2 / TiO2 double-layer film, by adjusting the thickness of TiO2 layer to control Zr x W y V 1-x-y The reflectivity of O2 / TiO2 film in the visible-near infrared band is improved, thereby improving the optical modulation performance of the film. In addition, TiO2 film can also protect Zr x W y V 1-x-y O2 is not oxidized, which enhances the stability of the film.

[0025] Compared with the prior art, the high stability Zr x W y V 1-x-y O2 / TiO2 double-layer film has the following beneficial effects:

[0026] (1) A high-stability ZrO2 smart window coating provided by the present invention x W y V 1-x-yThe O2 / TiO2 double-layer film has the characteristics of metal-insulator transition (i.e., IMT phase transition), and its metal-insulator transition temperature is close to room temperature, between 40°C and 45°C.

[0027] (2) A high-stability ZrO2 for smart window coating provided by the present invention x W y V 1-x-y The transmittance of the O2 / TiO2 double-layer film to visible light in the wavelength range of 380nm-780nm is 45%-65%, the modulation capacity to infrared light in the wavelength range of 780nm-2500nm is 15%-25%, and the modulation capacity to sunlight in the wavelength range of 300nm-2500nm is 8%-15%.

[0028] (3) A high-stability ZrO2 for smart window coating provided by the present invention x W y V 1-x-y The O2 / TiO2 double-layer film has high stability, and the performance of the sample after being stored in the atmospheric environment for 6 months has no significant change compared with the initial sample performance.

[0029] (4) A high-stability ZrO2 for smart window coating provided by the present invention x W y V 1-x-y The preparation process of O2 / TiO2 double-layer film is simple, has low environmental requirements, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The Zr grown on the c-plane sapphire substrate of the present invention x W y V 1-x-y Schematic diagram of the structure of O2 / TiO2 double-layer film.

[0031] Figure 2 The Zr prepared in Example 1 of the present invention 0.12 W 0.02 V 0.86 XRD pattern of O2 / TiO2 (150nm) double-layer film.

[0032] Figure 3 The Zr prepared in Example 1 of the present invention 0.12 W 0.02 V 0.86 The transmittance of O2 / TiO2 (150nm) double-layer film changes with temperature at a wavelength of 2500nm.

[0033] Figure 4 The Zr prepared in Example 1 of the present invention 0.12 W 0.02V 0.86 The transmittance versus temperature differential curve of O2 / TiO2 (150nm) double-layer film at a wavelength of 2500nm.

[0034] Figure 5 The Zr prepared in Example 1 of the present invention 0.12 W 0.02 V 0.86 Transmission spectrum of O2 / TiO2 (150nm) double-layer film.

[0035] Figure 6 The Zr prepared in Example 1 of the present invention 0.12 W 0.02 V 0.86 Transmission spectrum of O2 / TiO2 (150nm) double-layer film after being placed in the atmosphere for 6 months.

[0036] Figure 7 The Zr prepared in Example 2 of the present invention 0.12 W 0.02 V 0.86 XRD pattern of O2 / TiO2 (125nm) double-layer film.

[0037] Figure 8 The Zr prepared in Example 2 of the present invention 0.12 W 0.02 V 0.86 The transmittance of O2 / TiO2 (125nm) double-layer film changes with temperature at a wavelength of 2500nm.

[0038] Fig. 9 The Zr prepared in Example 2 of the present invention 0.12 W 0.02 V 0.86 The transmittance versus temperature differential curve of O2 / TiO2 (125nm) double-layer film at a wavelength of 2500nm.

[0039] Fig.10 The Zr prepared in Example 2 of the present invention 0.12 W 0.02 V 0.86 Transmission spectrum of O2 / TiO2 (125nm) double-layer film.

[0040] Fig.11 The Zr prepared in Example 2 of the present invention 0.12 W 0.02 V 0.86 Transmission spectrum of O2 / TiO2 (125nm) double-layer film after being placed in the atmosphere for 6 months.

[0041] Fig.12The Zr prepared in Comparative Example 1 of the present invention 0.12 W 0.02 V 0.86 XRD pattern of O2 functional film.

[0042] Fig.13 The Zr prepared in Comparative Example 1 of the present invention 0.12 W 0.02 V 0.86 Resistivity variation of O2 functional film with temperature.

[0043] Fig.14 The Zr prepared in Comparative Example 1 of the present invention 0.12 W 0.02 V 0.86 Resistivity versus temperature differential curve of O2 functional film.

[0044] Fig.15 The Zr prepared in Comparative Example 1 of the present invention 0.12 W 0.02 V 0.86 Transmission spectra of O2 functional films.

[0045] Fig.16 The Zr prepared in Comparative Example 2 of the present invention 0.13 W 0.025 V 0.845 XRD pattern of O2 functional film.

[0046] Fig.17 The Zr prepared in Comparative Example 2 of the present invention 0.13 W 0.025 V 0.845 Resistivity variation of O2 functional film with temperature.

[0047] Fig.18 The Zr prepared in Comparative Example 2 of the present invention 0.13 W 0.025 V 0.845 Resistivity versus temperature differential curve of O2 functional film.

[0048] Fig.19 The Zr prepared in Comparative Example 2 of the present invention 0.13 W 0.025 V 0.845 Transmission spectra of O2 functional films.

[0049] Fig. 20 It is the XRD spectrum of the VO2 functional film prepared in Comparative Example 3 of the present invention.

[0050] Fig.21 This is a graph showing the resistivity variation with temperature of the VO2 functional film prepared in Comparative Example 3 of the present invention.

[0051] Fig. 22 This is a resistivity versus temperature differential curve of the VO2 functional film prepared in Comparative Example 3 of the present invention.

[0052] Fig.23 It is the transmission spectrum of the VO2 functional film prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0053] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.

[0054] In order to better understand the present invention but not to limit the scope of the present invention, all the numbers used in this application to express the dosage, time, percentage, and other numerical values ​​should be understood as modified by the word "about" in all cases. Therefore, unless otherwise specified, all the numerical parameters listed in the specification and the appended claims are approximate values, which may be changed according to the different ideal properties attempted to be obtained. Each numerical parameter should at least be regarded as obtained according to the reported significant figures and by conventional rounding methods.

[0055] It should be noted that the high stability Zr x W y V 1-x-y O2 / TiO2 double-layer film, Zr prepared by the present invention x W y V 1-x-y The O2 / TiO2 double-layer film uses the characteristic that the band gap of ZrO2 (5eV) is larger than the band gap of VO2 (2.5eV). 4+ Ion partially replaces V 4+ ions to increase the optical band gap of VO2, thereby effectively improving the visible light transmittance of the film. 6+ Doping increases Zr x W y V 1-x-y The electron concentration of the O2 film makes it easier for the film to transition from the insulating phase to the metallic phase, thereby achieving the purpose of lowering the phase transition temperature of the film. x W y V 1-x-y O2 thin film optical modulation performance, the present invention is in Zr x Wy V 1-x-y Based on the O2 functional film, a TiO2 anti-reflection layer is introduced to construct a Zr x W y V 1-x-y O2 / TiO2 double-layer film, by adjusting the thickness of TiO2 layer to control Zr x W y V 1-x-y The reflectivity of O2 / TiO2 film in the visible-near infrared band is improved, thereby improving the optical modulation performance of the film. In addition, TiO2 film can also protect Zr x W y V 1-x-y O2 is not oxidized, which enhances the stability of the film.

[0056] Example 1

[0057] The invention provides a high-stability Zr for smart coatings. 0.12 W 0.02 V 0.86 O2 / TiO2 (150nm) double-layer film, the preparation method is as follows:

[0058] Using c-plane sapphire as the substrate, the substrate was ultrasonically cleaned for 15 minutes using cleaning solutions such as acetone, ethanol, and deionized water. After ultrasonic cleaning, the substrate was blown dry with nitrogen and immediately placed in the vacuum chamber of the pulsed laser deposition system. Subsequently, pulsed laser deposition was used, with Zr and W co-doped V2O5 ceramics as the target material. The distance between the target stage and the sample stage was set to 55 mm, the substrate temperature was 700 ° C, the vacuum chamber oxygen pressure was 1.5 Pa, the laser pulse energy was 300 mJ / pulse, the pulse laser frequency was 5 Hz, the sample stage and target stage rotation speeds were 10 r / min and 5 r / min respectively, and the deposition time was 30 min. Zr was grown. 0.12 W 0.02 V 0.86 The thickness of the O2 functional thin film layer is about 70nm. After the vacuum chamber is naturally cooled to room temperature, the target material is switched to a TiO2 ceramic target, the vacuum chamber oxygen pressure is set to 1Pa, the laser pulse energy is 240mJ / pulse, the pulse laser frequency is 5Hz, the sample stage and target stage rotation speeds are 10r / min and 5r / min respectively, and the Zr 0.12 W 0.02 V 0.86 A TiO2 film is grown on the surface of the O2 functional film layer. The deposition time is 60 minutes and the thickness of the TiO2 film is 150 nm.

[0059] Specifically, the preparation method of the Zr and W co-doped V2O5 ceramic target in the embodiment of the present application includes:

[0060] According to the molar ratio of n(ZrO2):n(WO3):n(V2O5)=40:2:179, 0.779g ZrO2 powder, 0.073g WO3 powder and 5.147g V2O5 powder were weighed and put into a ball mill, mixed evenly, 4-5g anhydrous ethanol was added, and then the ball mill was placed in a planetary ball mill for 4h to obtain a mixed powder;

[0061] The mixed powder was placed in a vacuum drying oven and vacuum dried at 80°C for 10 h. After being taken out, it was naturally cooled to room temperature. After being fully ground with a mortar, it was pressed into a circular green tablet with a diameter of 27.5 mm and a thickness of 2 mm using a tablet press at a pressure of 8 MPa.

[0062] The circular green sheet is placed in a crucible, and powders of the same composition are placed around it. The green sheet is sintered in a tube furnace at a temperature of 620°C for 6 hours, and then naturally cooled to room temperature to obtain Zr and W co-doped V2O5 ceramics.

[0063] Structure and performance test:

[0064] The high stability Zr prepared in this embodiment 0.12 W 0.02 V 0.86 The XRD spectrum of O2 / TiO2 (150nm) double-layer film is as follows Figure 2 As shown, there are two diffraction peaks in the full spectrum, the peak at 41.7° is the (0006) crystal plane diffraction peak of the c-Al2O3 substrate (JCPDS File No.46-1212), and the peak at 39.7° is the (020) crystal plane diffraction peak of M1-VO2 (JCPDS File No.43-1051). There are no other miscellaneous peaks in the spectrum, indicating that the prepared TiO2 is amorphous.

[0065] Figure 3 The Zr prepared in this example 0.12 W 0.02 V 0.86 The transmittance of the O2 / TiO2 (150nm) double-layer film changes with temperature at a wavelength of 2500nm. As can be seen from the figure, at a wavelength of 2500nm, the difference between the high and low temperature transmittance of the sample is 36.2%, indicating that the sample has a good infrared switching effect; in order to further determine the critical phase transition temperature of the film, the curve of the sample transmittance changing with temperature is then differentiated, and the results are as follows Figure 4 As shown, from Figure 4 It can be seen that Zr 0.12 W 0.02 V 0.86 The phase transition temperature of O2 / TiO2 (150nm) double-layer film is 45℃.

[0066] Figure 5 The Zr prepared in this example 0.12 W 0.02 V 0.86 Transmission spectrum of O2TiO2 (150nm) double-layer film. According to the actual solar irradiance, the transmittance of the film to visible light, infrared light and sunlight before and after the phase change is calculated by integration, and the modulation rate of the film to infrared light and sunlight is further calculated. The results show that the Zr prepared in this example 0.12 W 0.02 V 0.86 O2 / TiO2 (150nm) double-layer film has high visible light transmittance (T lum =50.7%), and has good infrared light control capability in the wavelength range of 780-2500nm (△T IR =19.8%), and has excellent sunlight control capability in the wavelength range of 300-2500nm (△T sol =11%).

[0067] The Zr prepared in this example 0.12 W 0.02 V 0.86 After the O2 / TiO2 (150nm) double-layer film was placed in the atmosphere for 6 months, its transmittance in the wavelength range of 300-2500nm did not change significantly ( Figure 6 ), indicating that the Zr prepared in this example 0.12 W 0.02 V 0.86 The O2 / TiO2 double-layer film has very high stability and meets the practical application requirements of smart windows.

[0068] Example 2

[0069] The invention provides a high-stability Zr for smart coatings. 0.12 W 0.02 V 0.86 O2 / TiO2 (125nm) double-layer film, the preparation method is as follows:

[0070] Using c-plane sapphire as the substrate, the substrate was ultrasonically cleaned for 15 minutes using cleaning solutions such as acetone, ethanol, and deionized water. After ultrasonic cleaning, the substrate was blown dry with nitrogen and immediately placed in the vacuum chamber of the pulsed laser deposition system. Subsequently, pulsed laser deposition was used, with Zr and W co-doped V2O5 ceramics as the target material. The distance between the target stage and the sample stage was set to 55 mm, the substrate temperature was 700 ° C, the vacuum chamber oxygen pressure was 1.5 Pa, the laser pulse energy was 300 mJ / pulse, the pulse laser frequency was 5 Hz, the sample stage and target stage rotation speeds were 10 r / min and 5 r / min respectively, and the deposition time was 30 min. Zr was grown. 0.02 W0.12 V 0.86 The thickness of the O2 functional thin film layer is about 70nm. After the vacuum chamber is naturally cooled to room temperature, the target material is switched to a TiO2 ceramic target, the vacuum chamber oxygen pressure is set to 1Pa, the laser pulse energy is 240mJ / pulse, the pulse laser frequency is 5Hz, the sample stage and target stage rotation speeds are 10r / min and 5r / min respectively, and the Zr 0.12 W 0.02 V 0.86 The O2 functional thin film layer grows a TiO2 thin film, the deposition time is 50 minutes, and the thickness of the TiO2 film is 125nm.

[0071] Specifically, the preparation method of the Zr and W co-doped V2O5 ceramic target in the embodiment of the present application includes:

[0072] According to the molar ratio of n(ZrO2):n(WO3):n(V2O5)=40:2:179, 0.779g ZrO2 powder, 0.073g WO3 powder and 5.147g V2O5 powder were weighed and put into a ball mill, mixed evenly, 4-5g anhydrous ethanol was added, and then the ball mill was placed in a planetary ball mill for 4h to obtain a mixed powder;

[0073] The mixed powder was placed in a vacuum drying oven and vacuum dried at 80°C for 10 h. After being taken out, it was naturally cooled to room temperature. After being fully ground with a mortar, it was pressed into a circular green tablet with a diameter of 27.5 mm and a thickness of 2 mm using a tablet press at a pressure of 8 MPa.

[0074] The circular green sheet is placed in a crucible, and powders of the same composition are placed around it. The green sheet is sintered in a tube furnace at a temperature of 620°C for 6 hours, and then naturally cooled to room temperature to obtain Zr and W co-doped V2O5 ceramics.

[0075] Structure and performance test:

[0076] The high stability Zr prepared in this embodiment 0.12 W 0.02 V 0.86 The XRD spectrum of O2 / TiO2 (125nm) double-layer film is as follows Figure 7 As shown, there are two diffraction peaks in the full spectrum, the peak at 41.7° is the (0006) crystal plane diffraction peak of the c-Al2O3 substrate (JCPDS File No.46-1212), and the peak at 39.7° is the (020) crystal plane diffraction peak of M1-VO2 (JCPDS File No.43-1051). There are no other miscellaneous peaks in the spectrum, indicating that the prepared TiO2 is amorphous.

[0077] Figure 8The Zr prepared in this example 0.12 W 0.02 V 0.86 The transmittance of the O2 / TiO2 (125nm) double-layer film at 2500nm wavelength varies with temperature. As can be seen from the figure, at 2500nm wavelength, the difference between the high and low temperature transmittance of the sample is 49.6%, indicating that the sample has a good infrared switching effect; in order to further determine the critical phase transition temperature of the film, the curve of the sample transmittance varying with temperature is then differentiated, and the results are as follows: Fig. 9 As shown, from Fig. 9 It can be seen that Zr 0.12 W 0.02 V 0.86 The phase transition temperature of O2 / TiO2 (125nm) double-layer film is 43.3℃.

[0078] Fig.10 The Zr prepared in this example 0.12 W 0.02 V 0.86 Transmission spectrum of O2 / TiO2 (125nm) double-layer film. According to the actual solar irradiance, the transmittance of the film to visible light, infrared light and sunlight before and after the phase change is calculated by integration, and the modulation rate of the film to infrared light and sunlight is further calculated. The results show that the Zr prepared in this example 0.12 W 0.02 V 0.86 The O2 / TiO2 (125nm) double-layer film has high visible light transmittance (T lum =57.6%), and has good infrared light control capability in the wavelength range of 780-2500nm (△T IR =15.9%), and has excellent sunlight control capability in the wavelength range of 300-2500nm (△T sol =9.4%).

[0079] The Zr prepared in this example 0.12 W 0.02 V 0.86 After the O2 / TiO2 (125nm) double-layer film was placed in the atmosphere for 6 months, its transmittance in the wavelength range of 780-2500nm did not change significantly, and the visible light transmittance in the wavelength range of 380-780nm decreased slightly ( Fig.11 ), indicating that the Zr prepared in this example 0.12 W 0.02 V 0.86 The O2 / TiO2 double-layer film has very high stability and meets the practical application requirements of smart windows.

[0080] Comparative Example 1

[0081] This comparative example is a single-layer functional thin film material, the chemical formula of the thin film is: Zr 0.12 W 0.02 V 0.86 O2, the preparation method thereof is as follows:

[0082] Using c-plane sapphire as the substrate, the substrate was ultrasonically cleaned for 15 minutes using cleaning solutions such as acetone, ethanol, and deionized water. After ultrasonic cleaning, the substrate was blown dry with nitrogen and immediately placed in the vacuum chamber of the pulsed laser deposition system. Subsequently, pulsed laser deposition was used, with Zr and W co-doped V2O5 ceramics as the target material. The distance between the target stage and the sample stage was set to 55 mm, the substrate temperature was 700 ° C, the vacuum chamber oxygen pressure was 1.5 Pa, the laser pulse energy was 300 mJ / pulse, the pulse laser frequency was 5 Hz, the sample stage and target stage rotation speeds were 10 r / min and 5 r / min respectively, and the deposition time was 30 min. Zr was grown. 0.12 W 0.02 V 0.86 O2 functional film, the thickness of the film layer is about 70nm.

[0083] Specifically, the preparation method of the Zr and W co-doped V2O5 ceramic target in this comparative example includes:

[0084] According to the molar ratio of n(ZrO2):n(WO3):n(V2O5)=40:2:179, 0.779g ZrO2 powder, 0.073g WO3 powder and 5.147g V2O5 powder were weighed and put into a ball mill, mixed evenly, 4-5g anhydrous ethanol was added, and then the ball mill was placed in a planetary ball mill for 4h to obtain a mixed powder;

[0085] The mixed powder was placed in a vacuum drying oven and vacuum dried at 80°C for 10 h. After being taken out, it was naturally cooled to room temperature. After being fully ground with a mortar, it was pressed into a circular green tablet with a diameter of 27.5 mm and a thickness of 2 mm using a tablet press at a pressure of 8 MPa.

[0086] The circular green sheet is placed in a crucible, and powders of the same composition are placed around it. The green sheet is sintered in a tube furnace at a temperature of 620°C for 6 hours, and then naturally cooled to room temperature to obtain Zr and W co-doped V2O5 ceramics.

[0087] Structure and performance test:

[0088] This comparative example produces Zr 0.02 W 0.12 V 0.86 The XRD spectrum of O2 functional film is as follows Fig.12As shown, there are two diffraction peaks in the full spectrum, the peak at 41.7° is the (0006) crystal plane diffraction peak of the c-Al2O3 substrate (JCPDS File No.46-1212), and the peak at 39.7° is the (020) crystal plane diffraction peak of M1-VO2 (JCPDS File No.43-1051). There are no other miscellaneous peaks in the spectrum.

[0089] Fig.13 The Zr prepared in this comparative example 0.12 W 0.02 V 0.86 The resistivity of O2 functional film varies with temperature. 0.12 W 0.02 V 0.86 The resistivity of the O2 functional film changes by about two orders of magnitude at high and low temperatures, indicating that the sample has good IMT phase transition characteristics. In order to further determine the critical phase transition temperature of the film, the curve of the resistivity of the sample changing with temperature is then differentiated. The results are as follows: Fig.14 As shown, from Fig.14 It can be seen that Zr 0.12 W 0.02 V 0.86 The phase transition temperature of the O2 functional film is 40.3℃.

[0090] Fig.15 This comparative example produces Zr 0.12 W 0.02 V 0.86 Transmission spectrum of O2 functional film. According to the actual solar irradiance, the transmittance of the film to visible light, infrared light and sunlight before and after the phase change is calculated by integration, and the modulation rate of the film to infrared light and sunlight is further calculated. The results show that the Zr 0.12 W 0.02 V 0.86 O2 functional film has high visible light transmittance (T lum =47.2%), and has good infrared light control capability in the wavelength range of 780-2500nm (△T IR =18.1%), and has excellent sunlight control capability in the wavelength range of 300-2500nm (△T sol =7.3%).

[0091] Comparative Example 2

[0092] This comparative example is a single-layer functional thin film material, the chemical formula of the thin film is: Zr 0.13 W 0.025 V 0.845 O2, the preparation method thereof is as follows:

[0093] Using c-plane sapphire as the substrate, the substrate was ultrasonically cleaned for 15 minutes using cleaning solutions such as acetone, ethanol, and deionized water. After ultrasonic cleaning, the substrate was blown dry with nitrogen and immediately placed in the vacuum chamber of the pulsed laser deposition system. Subsequently, pulsed laser deposition was used, with Zr and W co-doped V2O5 ceramics as the target material. The distance between the target stage and the sample stage was set to 55 mm, the substrate temperature was 700 ° C, the vacuum chamber oxygen pressure was 1.5 Pa, the laser pulse energy was 300 mJ / pulse, the pulse laser frequency was 5 Hz, the sample stage and target stage rotation speeds were 10 r / min and 5 r / min respectively, and the deposition time was 30 min. Zr was grown. 0.13 W 0.025 V 0.845 O2 functional film, the thickness of the film layer is about 70nm.

[0094] Specifically, the preparation method of the Zr and W co-doped V2O5 ceramic target in this comparative example includes:

[0095] At a molar ratio of n(ZrO2):n(WO3):n(V2O5)=20:2:89, 0.77g ZrO2 powder, 0.15g WO3 powder and 5.08g V2O5 powder were weighed and placed in a ball mill, mixed evenly, 4-5g anhydrous ethanol was added, and then the ball mill was placed in a planetary ball mill for 4h to obtain a mixed powder;

[0096] The mixed powder was placed in a vacuum drying oven and vacuum dried at 80°C for 10 h. After being taken out, it was naturally cooled to room temperature. After being fully ground with a mortar, it was pressed into a circular green tablet with a diameter of 27.5 mm and a thickness of 2 mm using a tablet press at a pressure of 8 MPa.

[0097] The circular green sheet is placed in a crucible, and powders of the same composition are placed around it. The green sheet is sintered in a tube furnace at a temperature of 620°C for 6 hours, and then naturally cooled to room temperature to obtain Zr and W co-doped V2O5 ceramics.

[0098] Structure and performance test:

[0099] This comparative example produces Zr 0.13 W 0.025 V 0.845 The XRD spectrum of O2 functional film is as follows Fig.16 As shown, there are two diffraction peaks in the full spectrum, the peak at 41.7° is the (0006) crystal plane diffraction peak of the c-Al2O3 substrate (JCPDS File No.46-1212), and the peak at 39.7° is the (020) crystal plane diffraction peak of M1-VO2 (JCPDS File No.43-1051). There are no other miscellaneous peaks in the spectrum.

[0100] Fig.17 The Zr prepared in this comparative example 0.13 W 0.025 V 0.845 The resistivity of O2 functional film varies with temperature. 0.13 W 0.025 V 0.845 The resistivity of the O2 functional film changes by about two orders of magnitude at high and low temperatures, indicating that the sample has good IMT phase transition characteristics. In order to further determine the critical phase transition temperature of the film, the curve of the resistivity of the sample changing with temperature is then differentiated. The results are as follows: Fig.18 As shown, from Fig.18 It can be seen that Zr 0.13 W 0.025 V 0.845 The phase transition temperature of O2 functional film is close to room temperature (T c =34.7°C).

[0101] Fig.19 This comparative example produces Zr 0.13 W 0.025 V 0.845 Transmission spectrum of O2 functional film. According to the actual solar irradiance, the transmittance of the film to visible light, infrared light and sunlight before and after the phase change is calculated by integration, and the modulation rate of the film to infrared light and sunlight is further calculated. The results show that the Zr 0.13 W 0.025 V 0.845 The O2 functional film has a high visible light transmittance (T lum =46.3%), and has good infrared light control capability in the wavelength range of 780-2500nm (△T IR =16.1%), and has good sunlight control capability in the wavelength range of 300-2500nm (△T sol =5.9%).

[0102] Comparative Example 3

[0103] This comparative example is a functional thin film material, the chemical formula of the thin film is VO2, and the preparation method thereof is as follows:

[0104] The c-plane sapphire was used as the substrate, and the substrate was ultrasonically cleaned for 15 minutes using cleaning solutions such as acetone, ethanol, and deionized water. After ultrasonic cleaning, the substrate was blown dry with nitrogen and immediately placed in the vacuum chamber of the pulsed laser deposition system. Subsequently, the pulsed laser deposition method was used, with V2O5 ceramics as the target material, and the distance between the target stage and the sample stage was set to 55mm, the substrate temperature was 650℃, the vacuum chamber oxygen pressure was 1.2Pa, the laser pulse energy was 300mJ / pulse, the pulse laser frequency was 5Hz, the sample stage and the target stage rotation speed were 10r / min and 5r / min respectively, and the deposition time was 30min. The VO2 functional film was grown, and the thickness of the film layer was about 75nm.

[0105] Specifically, the preparation method of the V2O5 ceramic target in this comparative example includes:

[0106] Weigh 6 g of V2O5 powder and put it in a ball mill, add 4-5 g of anhydrous ethanol, and then place the ball mill in a planetary ball mill for 4 hours to obtain a uniform powder;

[0107] The V2O5 powder was placed in a vacuum drying oven and vacuum dried at 80°C for 10 h. After being taken out, it was naturally cooled to room temperature. After being fully ground with a mortar, it was pressed into a round tablet with a diameter of 27.5 mm and a thickness of 2 mm using a tablet press at a pressure of 8 MPa.

[0108] The circular green sheet is placed in a crucible, and powders of the same composition are placed around it. The green sheet is sintered in a tube furnace at a temperature of 620°C for 6 hours, and then naturally cooled to room temperature to obtain V2O5 ceramics.

[0109] Structure and performance test:

[0110] The XRD spectrum of the VO2 functional film obtained in this comparative example is as follows Fig. 20 As shown, there are two diffraction peaks in the full spectrum, the peak at 41.7° is the (0006) crystal plane diffraction peak of the c-Al2O3 substrate (JCPDS File No.46-1212), and the peak at 39.7° is the (020) crystal plane diffraction peak of M1-VO2 (JCPDS File No.43-1051). There are no other miscellaneous peaks in the spectrum.

[0111] Fig.21 This is the resistivity variation spectrum of the VO2 functional film prepared in this comparative example. As can be seen from the figure, the resistivity of the VO2 functional film changes by about two orders of magnitude at high and low temperatures, indicating that the sample has good IMT phase transition characteristics; in order to further determine the critical phase transition temperature of the film, the curve of the resistivity variation of the sample with temperature is then differentiated, and the results are as follows: Fig. 22 As shown, from Fig. 22It can be seen that the phase transition temperature of VO2 functional film is 70.2℃.

[0112] Fig.23 is the transmission spectrum of the VO2 functional film obtained in this comparative example. According to the actual solar irradiance, the transmittance of the film to visible light, infrared light and sunlight before and after the phase change is calculated by integration, and the modulation rate of the film to infrared light and sunlight is further calculated. The results show that the VO2 functional film obtained in this comparative example has a low visible light transmittance (T lum =37.3%), and has good infrared light control capability in the wavelength range of 780-2500nm (△T IR =22.5%), and has excellent sunlight control capability in the wavelength range of 300-2500nm (△T sol =9.7%).

Claims

1. A high-stability Zr for smart window coatings x W y V 1-x-y O2 / TiO2 double-layer film and preparation method thereof, characterized in that: Zr x W y V 1-x-y O2 / TiO2 double-layer film including Zr x W y V 1-x-y O2 functional layer and TiO2 anti-reflection layer, wherein 0<x<1, 0<y<1.

2. A high stability Zr for smart window coating as claimed in claim 1 x W y V 1-x-y O2 / TiO2 double-layer film and preparation method thereof, characterized in that: Zr x W y V 1-x-y The specific steps for preparing O2 / TiO2 double-layer film are as follows: (1) Select a suitable substrate and perform ultrasonic cleaning on the substrate using acetone, ethanol, and deionized water in sequence, with each cleaning time fixed at 15 min. After cleaning, blow dry the substrate using nitrogen; (2) Preparation of Zr on the pretreated substrate surface x W y V 1-x-y O2 functional thin film layer; (3) In Zr x W y V 1-x-y TiO2 is deposited on the O2 functional layer as an anti-reflection layer to obtain Zr x W y V 1-x-y O2 / TiO2 double-layer film.

3. A high stability Zr for smart window coating as claimed in claim 2 x W y V 1-x-y O2 / TiO2 double-layer film and preparation method thereof, characterized in that: The substrate in step (1) is a c-plane sapphire substrate or a glass substrate.

4. A high stability Zr for smart window coating as claimed in claim 2 x W y V 1-x-y O2 / TiO2 double-layer film and preparation method thereof, characterized in that: Step (2) and step (3) wherein Zr x W y V 1-x-y The O2 functional thin film layer and the TiO2 anti-reflection layer can be prepared by pulse laser deposition, magnetron sputtering or electron beam evaporation.

5. A high stability Zr for smart window coating as claimed in claim 2 x W y V 1-x-y O2 / TiO2 double-layer film and preparation method thereof, characterized in that: The Zr x W y V 1-x-y The specific steps of O2 / TiO2 double-layer film are as follows: (a) Using Zr and W co-doped V2O5 ceramics as the target, the target and substrate are placed in a vacuum chamber and evacuated to 10 -3 ~10 -4 The temperature of the substrate is controlled to be 300-800°C, the pulse laser energy is controlled to be 200-600mJ / Pulse, the oxygen pressure is controlled to be 0-10Pa, and the Zr is deposited on the surface of the substrate. x W y V 1-x-y O2 functional film; (b) TiO2 ceramics are used as the target material, the substrate temperature is controlled to be 25-200°C, the pulse laser energy is controlled to be 200-600 mJ / Pulse, the oxygen pressure is controlled to be 0-10 Pa, and x W y V 1-x-y The TiO2 anti-reflection layer film is obtained by depositing the TiO2 film on the surface of the film.

6. A high stability Zr for smart window coating as claimed in claim 5 x W y V 1-x-y O2 / TiO2 double-layer film and preparation method thereof, characterized in that: The preparation method of the Zr and W co-doped V2O5 ceramic in step (a) is as follows: Weigh ZrO2, WO3, and V2O5 powders according to the molar ratio and place them in a ball mill. After mixing evenly, place them in a planetary ball mill and mill for 4 to 6 hours to obtain a mixed powder. The mixed powder is placed in a vacuum drying oven at 80-120° C. for 10-12 hours, then crushed and pressed into round tablets; The disc is placed in a vacuum tube furnace and sintered at 600-700° C. for 6-8 hours to obtain Zr and W co-doped V2O5 ceramics.

7. A high stability Zr for smart window coating as claimed in claim 5. x W y V 1-x-y O2 / TiO2 double-layer film and preparation method thereof, characterized in that : Step (a) Zr x W y V 1-x-y The deposition time of O2 film is 30 to 60 minutes; The deposition time of the TiO2 anti-reflection layer in step (b) is 10 to 60 minutes.

8. A high stability Zr for smart window coating as claimed in claim 5 x W y V 1-x-y O2 / TiO2 double-layer film and preparation method thereof, characterized in that : Step (a) Zr x W y V 1-x-y The thickness of O2 film is 70-110nm; The thickness of the TiO2 anti-reflection layer in step (b) is 0 to 200 nm.